Bit‐error‐rate performance of high‐order APPM and AOPPM for non‐Kolmogorov gamma–gamma channel FSO communications. Issue 4 (24th November 2020) - Xu, Meiyong; Ullah, Sibghat; Zhang, Sihan; Yuan, Deyu; Fu, Xiujia; Wang, Kaimin; Xin, Xiangjun
Abstract: High‐order pulse modulations in free space optics (FSO) communication are of practical value, and non‐Kolmogorov gamma–gamma (GG) channel model is the most suitable for FSO channel. However, research on a system combined with the above is rarely reported. In our work, we propose high‐order (4*32 and 4*64) amplitude and pulse position modulation (APPM) and overlapping amplitude and pulse position modulation (AOPPM) FSO communication system under a modified non‐Kolmogorov GG turbulent channel model. Simulation results present that AOPPM is obviously better than APPM in bit‐error‐rate (BER) performance, and BER performance grows with the increase of modulation order (number of pulse positions). The proposed schemes may provide a reference for system design and practical application.